2018
DOI: 10.1140/epjc/s10052-018-6053-0
|View full text |Cite
|
Sign up to set email alerts
|

Consistency between dynamical and thermodynamical stabilities for perfect fluid in f(R) theories

Abstract: We investigate the stability criterions for perfect fluid in f (R) theories which is an important generalization of general relativity. Firstly, using Wald's general variation principle, we recast Seifert's work and obtain the dynamical stability criterion. Then using our generalized thermodynamical criterion, we obtain the concrete expressions of the criterion. We show that the dynamical stability criterion is exactly the same as the thermodynamical stability criterion to spherically symmetric perturbations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Roupas proved that the maximum of total entropy of perfect fluid is consistent with the dynamical stability obtained by Yabushita [17,18]. More recently, we show that the dynamical stability and thermodynamical stability are exactly the same both in general relativity or some modified theory such as f (R) theories [19,20].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Roupas proved that the maximum of total entropy of perfect fluid is consistent with the dynamical stability obtained by Yabushita [17,18]. More recently, we show that the dynamical stability and thermodynamical stability are exactly the same both in general relativity or some modified theory such as f (R) theories [19,20].…”
Section: Introductionsupporting
confidence: 86%
“…are always satisfied, where T and χ are the temperature of the fluid and the redshift factor of the static observer. It is showed that if the Lagrangian constructed purely by the metric and its derivatives, the second variation of total entropy under the perturbation can be written as a uniform expression [19,20],…”
Section: Thermodynamic Methodsmentioning
confidence: 99%
“…Thermodynamic descriptions of gravitational solutions at the event horizon and cosmological ones at the apparent horizon in F(R) gravity have been studied in series of papers [54][55][56][57][58][59][60][61][62] . In this work, we are going to evaluate thermodynamic phase transition of black hole solutions in a special class of F(R) gravity with constant Ricci scalar in which both F(R) and its derivative F R (R) are vanished in the field equations.…”
Section: Introductionmentioning
confidence: 99%
“…Gao extended their work to an arbitrary perfect fluid in a static spherical geometry [16], in which they only used some thermodynamical relations. After that, this principle has been widely studied by the researchers [17][18][19][20][21][22]. Their results showed the consistency between the ordinary thermodynamics of fluid and gravitational dynamics.…”
Section: Introductionmentioning
confidence: 92%